Amphiphilic Polyoxometalates for the Controlled Synthesis of Hybrid Polystyrene Particles with Surface Reactivity. Issue 7 (18th December 2014) - Lesage de La Haye, Jennifer; Guigner, Jean‐Michel; Marceau, Eric; Ruhlmann, Laurent; Hasenknopf, Bernold; Lacôte, Emmanuel; Rieger, Jutta
Abstract Amphiphilic organo‐polyoxometalates (POMs) used in the radical emulsion polymerization of styrene allowed the preparation in aqueous medium of stable 50–100 nm polystyrene–POM composite latexes. Thanks to the presence of a trithiocarbonate group in the POM amphiphile, POMs could be covalently linked to the polymer particle surface. The chemical and catalytic integrity of the POMs was confirmed, and the POM‐mediated surface photoactivity of the latexes was demonstrated by the spatially controlled nucleation of silver nanoparticles at the periphery of the composites.